INFORMATION ASYMMETRY AND PROFIT MANAGEMENT ON COST OF EQUITY CAPITAL - Astutik, Rika; Cahyono, Dwi; Fiel Afroh, Ibna Kamelia (The International Journal of Business Review (The Jobs Review), 2018)
This study aims to examine the effect of information asymmetry and earnings management on the cost of equity capital for food and beverages companies listed on the Indonesia Stock Exchange. The object in this study is food and beverages companies listed on the Indonesia Stock Exchange and the sample of research obtained by 11 companies with the study period is the 2015-2018 financial year. The independent variables used are information asymmetry and earnings management, while the dependent variable is cost of equity capital, moderating variables are agency theory and capital market theory. Data analysis method is done by using multiple regression calculations to examine the effect of independent variables on the dependent variable. The results of the study indicate that information asymmetry produces a non-significant positive direction and earnings management produces a positive direction significantly affecting the cost of equity capital. moderating variables of agency theory and capital market theory produce a non-significant positive direction on the relationship of information asymmetry on cost of equity capital. While the results of previous studies indicate that information asymmetry and earnings management have no effect on the cost of equity capital while other studies that show information asymmetry have a positive effect on earnings management practices while firm size has a negative effect on earnings management practices. Investors assess at this time, the company that issued new ordinary shares is to cover its operational and investment debt, so that the company is less attractive to investors. In addition, investors consider other things in investing in a company such as business decision making, not only focusing on earnings information asymmetry, but also considering non-financial information on the existence of the company's internal mechanism